Post hoc analysis of a randomized, double-blind, prospective trial evaluating a CXCR1/2 inhibitor in new-onset type 1 diabetes: endo-metabolic features at baseline identify a subgroup of responders - Sordi, Valeria; Monti, Paolo; Lampasona, Vito; Melzi, Raffaella; Pellegrini, Silvia; Keymeulen, Bart; Gillard, Pieter; Linn, Thomas; Bosi, Emanuele; Rose, Ludger; Pozzilli, Paolo; Giorgino, Francesco; et al. (Frontiers in Endocrinology, 2023)
Aim. In a recent randomized, multicenter trial (NCT02814838) a short-term anti-inflammatory treatment with ladarixin (LDX; an inhibitor of the CXCR1/2 chemokine receptors) did not show benefit on preserving residual beta cell function in new-onset type 1 diabetes. We present a post-hoc analysis of trial patients in the predefined subgroup analysis developed according to baseline daily insulin requirement (DIR) tertiles. Method. A double blind, randomized (2:1), placebo-controlled study was conducted in 45 males and 31 females (aged 18-46 years) within 100 days of the first insulin administration. Patients received LDX (400 mg twice daily) for three cycles of 14 days on/14 days off, or placebo. The primary endpoint was the area under the curve for C-peptide [AUC (0-120 min)] in response to a 2-hour mixed meal tolerance test (MMTT) at week 13 ± 1. Seventy-five patients completed the week 13 MMTT and were divided into 3 groups according to the DIR tertiles: lower, ≤ 0.23U/kg/die (n=25); middle, 0.24-0.40 U/kg/die (n=24); upper, ≥ 0.41 U/kg/die (n=26). Results. When considering the patients in the upper tertile (HIGH-DIR), C-peptide AUC (0-120 min) at 13 weeks was higher in the LDX group (n=16) than in the placebo (n=10) group [difference: 0.72 nmol/L (95% CI 0.9-1.34), p=0.027]. This difference reduced over time (0.71 nmol/L at 26 weeks, p= 0.04; 0.42 nmol/L at 52 weeks, p=0.29), while it has never been significant at any time in patients in the lower and/or middle tertile (LOW-DIR). We characterized at baseline the HIGH-DIR and found that endo-metabolic (HOMA-B, adiponectin and glucagon-to-C-peptide ratio) and immunologic (CCL2/MCP-1 and VEGF) features distinguished this group from LOW-DIR. Conclusion. While LDX did not prevent the progressive loss of beta-cell function in the majority of treated subjects, the post-hoc analysis suggests that it could work in subjects with HIGH-DIR at baseline. As we found differences in endo-metabolic and immunologic parameters within this subgroup, this generates the hypothesis that the interactions between host factors and drug action can contribute to its efficacy. Further research is needed to evaluate this hypothesis.